2016
DOI: 10.1016/j.aop.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Infinite matter properties and zero-range limit of non-relativistic finite-range interactions

Abstract: We discuss some infinite matter properties of two finite-range interactions widely used for nuclear structure calculations, namely Gogny and M3Y interactions. We show that some useful informations can be deduced for the central, tensor and spin-orbit terms from the spin-isospin channels and the partial wave decomposition of the symmetric nuclear matter equation of state. We show in particular that the central part of the Gogny interaction should benefit from the introduction of a third Gaussian and the tensor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 67 publications
(161 reference statements)
0
44
0
Order By: Relevance
“…The spin-orbit term V LS N1LO is not affected by the inclusion of higher order gradient terms: in Ref. [25], we have shown that other possible spin-orbit terms are suppressed once the local gauge invariance [3,33] is imposed. In Ref.…”
Section: N2lo Skyrme Functionalmentioning
confidence: 99%
“…The spin-orbit term V LS N1LO is not affected by the inclusion of higher order gradient terms: in Ref. [25], we have shown that other possible spin-orbit terms are suppressed once the local gauge invariance [3,33] is imposed. In Ref.…”
Section: N2lo Skyrme Functionalmentioning
confidence: 99%
“…Such a result does not change if we re-fit the parameters of the interaction by taking into account only SNM properties (see Ref. [10]) for details. The additional density dependent term of D1P and D1-AS is not of much help since it explicitly enters only in the (S=1,T=0) and (S=0,T=1) channel.…”
Section: Symmetric Nuclear Matter Equation Of Statementioning
confidence: 99%
“…The explicit expressions for Gogny interaction have been already given in Ref. [10] (for the interactions D1P and D1-AS, which have a slightly different density dependence, the results have been straigthforwardly generalised). The results are presented in Fig.2.…”
Section: Symmetric Nuclear Matter Equation Of Statementioning
confidence: 99%
See 2 more Smart Citations